A Life-Course Analysis of Military Service in Vietman - Wright, John Paul (Journal of research in crime and delinquency, 2005)
Prior research demonstrates that military service disconnects men from past social and personal disadvantages and thus potentially alters normal life-course patterns of development. Much of this research, however, has been conducted only with World War II veterans. Relatively few studies have examined the influence of military service in Vietnam and its impact on altering individual trajectories of development. Through latent growth curve models, the authors examine the impact of military service in Vietnam on drug use and arrests across the life-course. Longitudinal data collected by the Marion County Youth study 1964-1979 were used to track a sample of men over a 15-year period. Analyses of these data revealed substantial nonrandom selection effects associated with service in Vietnam. Lower-class youths with already established delinquent patterns were significantly more likely to have served in Vietnam. It also appears, however, that service in Vietnam significantly increased individual drug use and, hence, offending rates. ABSTRACT FROM AUTHOR